2023
DOI: 10.3390/molecules28031432
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Method for Determination of Seven Bisphenols in Human Breast Milk Samples with the Use of HPLC-FLD

Abstract: Plastic pollution, where bisphenol A (BPA) is widely used in its production, has gained popularity. BPA omnipresence and toxicity, especially for infants, has led food safety authorities to place restrictions on BPA usage. It has led to the introduction of the marked ‘BPA-free’-labelled products, where BPA is often replaced by other bisphenols (BPs) which are suspected of being similar or even more toxic than BPA. Moreover, the free forms of BPs are more dangerous than their conjugated forms and the conjugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The ubiquitous presence of bisphenols in the environment imposes a great threat to different aspects of human health including reproduction 49 . The occurrence of bisphenols was frequently reported in human samples such as in urine, blood, milk, placenta, and amniotic fluids 1–3,50 . BPS has been detected in the human urine samples at concentrations ranging from 0.02 to 21 ng/mL 51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ubiquitous presence of bisphenols in the environment imposes a great threat to different aspects of human health including reproduction 49 . The occurrence of bisphenols was frequently reported in human samples such as in urine, blood, milk, placenta, and amniotic fluids 1–3,50 . BPS has been detected in the human urine samples at concentrations ranging from 0.02 to 21 ng/mL 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…But recently BPS has emerged to be as an endocrine-disrupting chemical (EDC) found ubiquitously and even detected in human samples such as blood, urine, and breast milk. [1][2][3] Bisphenols negatively impact hypothalamo-pituitary-ovarian (HPO) axis and are a threat to female reproductive health. Reports suggested that exposure to different doses of bisphenols decreased GnRH, luteinizing hormone (LH), and folliclestimulating hormone (FSH) levels along with gonadal steroids such as estradiol and progesterone 4,5 leading to a decrease in ovarian aromatase expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is essential to find a simple and sensitive method for BP determination in environmental water. 5 HPLC is a common determination method for BPs because of its facile operation and low cost. However, efficient sample pretreatments are usually needed prior to analysis for the removal of interferents and concentration of analytes.…”
Section: Introductionmentioning
confidence: 99%